Aplicação do modelo calgary de avaliação familiar a pacientes com câncer em cuidados paliativos - Oliveira, Amanda Maritsa de Magalhães (2019)
Palliative care is a therapeutic modality applied by a multidisciplinary team for the benefit of the patient in the face of a life threatening illness, with a view to a care that reduces suffering, improves the quality of life and dignity of patients and their families. The Calgary Family Assessment Model (MCAF) as a theoretical methodological contribution to this study allows us to investigate the structural, functional and functional dimension of family dynamics, making it possible to identify weaknesses and strengths in the family support network of these cancer patients in palliative care. Objectives: To evaluate the structure, development and functionality of families of cancer patients in palliative care in the light of the Calgary Family Assessment Model. Method: this is a field study with a qualitative approach, embodied in the Calgary Model of Family Assessment, carried out in a philanthropic hospital in cancer care, located in the city of Recife, Pernambuco. The research sample consisted of ten patients and 10 relatives. In compliance with ethical observances, the project was evaluated and approved by the Research Ethics Committee of Pernambucana Society for the Fight against Cancer under CAAE no. 71835317.0.3001.5205. To collect data, we used the interview technique guided by two instruments proposed for the study: a sociodemographic and clinical characterization instrument, pertinent to oncological disease and a semistructured script of questions elaborated by the researchers, based on MCAF recommendations. The recorded interviews were transcribed in full. And it made possible the construction of the two instruments proposed by the MCAF, the genogram and the ecomap. The empirical material was analyzed qualitatively in light of the MCAF. Results: The results allowed the construction of two articles: 1- Palliative care for patients with head and neck cancer: a study based on the Calgary Model and 2- Family assessment of women with breast cancer in palliative care: an approach in the perspective of the Calgary Model. In both articles, the difficulties faced by patients and their relatives in life finitude situations were identified. We emphasize that the structural support network and the flow of energy among family members were, in large part, positive, which favored to preserve the patient's quality of life at this stage of life. Conclusions: The families participating in this study presented remodeling in their social and functional roles within the family group. The reorganization of roles was considered less strenuous in larger families than in smaller families. Strategies of unity,adequate communication and resilience based on spirituality have proved positive for alliative care. It should be noted that this study is only part of a reality cut, given the magnitude and complexity of palliative care. It is necessary to prepare new studies on palliative care for the cancer patient, family members, multiprofessional team, teachers, students, and managers of the palliative care area, with emphasis on the new nursing care models